'Oiling the social wheels' in an undergraduate chemistry lab: an ITA's participation in small talk. Issue 3 (2nd July 2020) - Aslan, Erhan
ABSTRACT: Even though small talk has been investigated in a variety of business contexts and service encounters, it is understudied in instructional settings. This paper explores the occurrence of small talk in a university chemistry lab between a Chinese international teaching assistant (ITA) and American students. Drawing on naturally occurring interaction data from a conversation analysis perspective, triangulated by interview data and researcher field notes, the study describes the particular functions of small talk, such as identity affiliation and rapport management through humorous small talk. The findings are discussed in relation to ITA identity and professional development and the role of small talk in instructional discourse.